Psychology's grand theorists : how personal experiences shaped professional ideas - Demorest, Amy (Lawrence Erlbaum Associates, 2005)
This book is based on the premise that the theories on which the three dominant schools in psychology are based - psychodynamics, behavioral, and phenomenological - resulted in part from the personal experiences of the theorists who first originated them - Freud for psychodynamics, B.F. Skinner for behavioral, and Carl Rogers for phenomenological.